Evaluation of anti-diabetic activity of Justicia adhatoda (Linn.) Leaves in diabetic wistar rats - Roshan Kumar Mehta; Rupkala Thapa; Mukesh Kumar Chaudhary (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTIONDiabetes mellitus is deﬁned as the increase in blood glucose level resulting from defects in insulin secretion, insulin action, or both. The present study was conducted to evaluate anti-diabetic activity of Justicia adhatoda (Linn.) leaves extract in diabetic Wistar rats. Justicia adhatoda, commonly known as vasaka is rich in phytochemicals like alkaloids, saponins, steroids, ﬂavonoids and glycosides. It is used in asthma, jaundice, wound healing, typhus fever, cough, chronic bronchitis and inﬂamma- tory swellings treatment.MATERIAL AND METHODSThe extract was obtained by maceration process with the use of methanol as solvent. 30 Wistar rats of 150-250 gm were used taken as study animal. Diabetes was induced by single intraperitoneal injection of Alloxan 150 mg/kg body weight. The methan- olic extract of low dose (50 mg/kg) and high dose (100 mg/kg) were given orally for anti-diabetic activity. The standard drug glimepiride 0.5 mg/kg body weight was used.RESULTSThe extract treated 50mg/kg and 100mg/kg showed signiﬁcant p